Effect of yoga on physical and various hematological parameters - Banerjee, Ashish Bijaykrishna; Banerjee, Anita Ashish; Sharma, Lokendra Kumar; Kumar, Susheel (International Journal Of Community Medicine And Public Health, 2019)
Background: Yoga is a physical, mental and spiritual practice that has been around since ages. With time, people have discovered a number of health benefits associated with yoga. Methods: This longitudinal interventional study intended to evaluate the effect of yoga intervention on physical health and various hematological parameters. Thirty five healthy individuals between the age group of 18 to 45 years participated in the study. After a written informed consent, the individuals underwent various types of yoga exercises for 90 days under supervision of professional yoga trainer. Impact on body mass index (BMI), pulse rate, blood pressure (BP), and various haematological parameters like hemoglobin percentage (Hb %), white blood cell (WBC) count, platelet count, were taken under consideration before and after training. Statistical analysis was performed using paired t-test. Results: Significant reduction in BMI, BP and rise in Hb % and platelet (p<0.05) was observed. However, although WBC count showed improvement, the difference was statistically non-significant. No adverse events were observed during the study period. Conclusions: The present study findings highlight the importance of yoga in improving physical health and hematological markers.